Organizational bases of resort medical centers with the of quality management systems - Titov, G. I.; Tomareva-Patlakhova, V. V.; Voloshin, V. A.; Zukow, W.; Gozhenko, O. A. (Journal of Education, Health and Sport, 2018)
With the introduction of a quality management system in spa health centers (sanatoria), opportunities for development and profitability are increasing. The organization of the structure of the medical center's work at the resort has its own peculiarities, which should be reflected in the routes of patients, the rules for the provision of medical care. The development of spa medical centers is reasonably feasible in the context of improving the infrastructure, taking into account the competitive advantages of the resort, introducing modern technology of treatment and marketing strategies.